Effect Of Lead Acetate (Pb(Ch3coo)2) On The Growth Of Marine Microalgae Porphyridium cruentum - Sanep, Jacqlien Virgina; Kemer, Kurniati; Mantiri, Desy M. H.; Paulus, James J. H.; Mamuaja, Jane M.; Tombokan, John L. (Sam Ratulangi University, 2023)
Microalgae are a group of phytoplankton that live in waters and in damp places; Microscopic in size and can only be seen with a microscope. The stages of microalgae growth are started with the lag phase, the exponential phase, the growth rate decreasing phase, the stationary phase, and the death phase. Porphyridium cruentum is a single-celled microalgae, belonging to the class Rhodophyceae, free-living or in colonies bound in mucilago. The purpose of this study was to observe the growth of the marine microalgae Porphyridium cruentum in culture media treated with lead acetate at different concentrations, namely 30 ppm, 50 ppm, 80 ppm, and control. Observation of cell growth was carried out by counting the number of cells every day, at the same time until Porphyridum cruentum entered the death phase. The cell density of Porphyridium cruentum marine microalgae showed a good growth pattern where until day 11 the average number of microalgae cells was 9.8 x104. Furthermore, the culture media was treated with lead acetate in different concentrations. Cell density with lead acetate treatment can affect the growth of Porphyridium cruentum. Keywords : Microalgae; Porphyridium cruentum; Lead Acetate Abstrak Mikroalga adalah kelompok fitoplankton yang hidup di perairan dan di tempat yang lembab; berukuran mikroskopis dan hanya bisa dilihat menggunakan mikroskop. Tahapan pertumbuhan mikroalga adalah dimulai dari fase lag, fase eksponensial, fase penurunan laju pertumbuhan, fase stasioner dan fase kematian. Porphyridium cruentum merupakan mikroalga bersel tunggal, termasuk kelas Rhodophyceae, hidup bebas atau berkoloni yang terikat dalam mucilago. Tujuan dari penelitian ini adalah mengamati pertumbuhan dari mikroalga laut Porphyridium cruentum pada media kultur dengan perlakuan timbal asetat pada konsentrasi berbeda yaitu 30 ppm, 50 ppm, 80 ppm dan kontrol. Pengamatan pertumbuhan sel dilakukan dengan menghitung jumlah sel setiap hari, pada waktu yang sama sampai Porphyridum cruentum memasuki fase kematian. Kepadatan sel mikroalga laut Porphyridium cruentum menunjukkan pola pertumbuhan yang baik dimana sampai hari ke 11 jumlah rata-rata sel mikroalga 9,8 x104. Selanjutnya media kultur diberi perlakuan timbal asetat dengan konsentrasi berbeda. Kepadatan sel dengan perlakuan timbal asetat dapat mempengaruhi pertumbuhan Porphyridium cruentum. Kata kunci: Mikroalga; Porphyridium cruentum; Timbal Asetat